Assessment of Noise from Different Types of Rounds Fired from a Saluting Gun - Gurmail S. PADDAN; Matt J. HOWELL (Archives of Acoustics)
The difference in sound pressure levels between two types of rounds fired from a saluting gun has been investigated; the rounds being identified as ‘current’ and ‘new’. A 3-pounder saluting gun mounted on a concrete floor based at HMNB Portsmouth, UK, was used in the survey. Sound pressure levels were measured at the two people responsible for operating the gun: the firer and the loader. Twelve current rounds and 24 new rounds were fired during the survey. The new rounds showed a greater variation in peak sound pressure levels between rounds (interquartile range of 2.1 dB, firer’s location) compared with the current rounds (interquartile range of 1.1 dB, firer’s location). The highest C-weighted peak sound pressure levels for the firer were 173.1 dB for the current round compared with 166.8 dB for the new round. The corresponding highest C-weighted peak sound pressure levels for the loader were 170.6 dB and 163.0 dB, respectively. The difference between median peak sound pressure levels was 8.8 dB for the firer and 9.8 dB for the loader. Similar differences were measured in sound exposure levels between the two types of rounds. Frequency data presented can be used for assessing the suitability of appropriate hearing protectors. Mitigation measures are proposed for further reducing noise exposure of the operators.